KECEMASAN KOMUNIKASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Latifah Latifah (Jurnal Terapung : Ilmu - Ilmu Sosial, 2021)
This study systematically changes student behavior in the communication anxiety of Islamic Religious Education teachers at Madrasah Ibtidaiyah Assalam Martapura. Focusing on changing behavior and helping teachers to implement good behavior for their students. This behavior change is communication anxiety in students in the learning process which can overcome fear, confusion, and confusion of thought, body shaking, and stage fright that arises in communicating.Keywords: communication anxiety, Islamic Religious Education learning